Factors associated with clinically significant hypoglycemia in patients with type 1 diabetes using sensor-augmented pump therapy with predictive low-glucose management: A multicentric study on iberoamerica. Issue 1 (January 2021) - Gómez, Ana M.; Imitola, Angelica; Henao, Diana; García-Jaramillo, Maira; Giménez, Marga; Viñals, Clara; Grassi, Bruno; Torres, Mariana; Zuluaga, Isabella; Muñoz, Oscar Mauricio; Rondón, Martin; León-Vargas, Fabián; et al.
Abstract: Background and aims: Despite using sensor-augmented pump therapy (SAPT) with predictive low-glucose management (PLGM), hypoglycemia is still an issue in patients with type 1 Diabetes (T1D). Our aim was to determine factors associated with clinically significant hypoglycemia (<54 mg/dl) in persons with T1D treated with PLGM-SAPT. Method: ology: This is a multicentric prospective real-life study performed in Colombia, Chile and Spain. Patients with T1D treated with PLGM-SAPT, using sensor ≥70% of time, were included. Data regarding pump and sensor use patterns and carbohydrate intake from 28 consecutive days were collected. A bivariate and multivariate Poisson regression analysis was carried out, to evaluate the association between the number of events of <54 mg/dl with the clinical variables and patterns of sensor and pump use. Results: 188 subjects were included (41 ± 13.8 years-old, 23 ± 12 years disease duration, A1c 7.2% ± 0.9). The median of events <54 mg/dl was four events/patient/month (IQR 1–10), 77% of these events occurred during day time. Multivariate analysis showed that the number of events of hypoglycemia were higher in patients with previous severe hypoglycemia (IRR1.38; 95% CI 1.19–1.61; p < 0.001), high glycemic variability defined as Coefficient of Variation (CV%) > 36% (IRR 2.09; 95%CI 1.79–2.45; p < 0.001) and hypoglycemia unawareness. A protector effect was identified for adequate sensor calibration (IRR 0.77; 95%CI 0.66–0.90; p:0.001), and the use of bolus wizard >60% (IRR 0.74; 95%CI 0.58–0.95; p:0.017). Conclusion: In spite of using advanced SAPT, clinically significant hypoglycemia is still a non-negligible risk. Only the identification and intervention of modifiable factors could help to prevent and reduce hypoglycemia in clinical practice. Highlights: Despite the use of advance sensor augmented pump therapy (SAPT), hypoglycemia remains a problem in type 1 diabetes. High glycemic variability, previous severe and unawareness hypoglycemia, were associated with hypoglycemic events. The intervention of factors such as sensor calibration and the use of bolus wizard could help to prevent hypoglycemia. This is the first multicenter study that describes variables associated with hypoglycemia in patients treated with SAPT.